Applied Theories: Using Linguistic and Literary Frameworks in Research - Hueso-Vasallo, Manuel; Pizarro, Margalida (My University, 2025)
This workshop aims to equip early-career researchers in Anglophone Studies with the tools to effectively integrate linguistic and literary theories into their academic work. Recognising the interdisciplinary nature of English Studies, the session will explore how theoretical frameworks can illuminate various facets of texts, from phonetics and syntax to narrative structures and cultural contexts. Through practical examples and guided exercises, participants will learn to select and apply appropriate theoretical lenses, enhancing the depth and clarity of their analyses. The workshop will also address common challenges faced by emerging scholars, such as navigating theoretical jargon and aligning theory with research objectives. By fostering a collaborative environment, the session encourages participants to share experiences and strategies, building a supportive community of practice within the ASYRAS network.
Keywords: Filología inglesa; Lingüística; Linguistic theory; Literary theories